2020
DOI: 10.1111/ijfs.14687
|View full text |Cite
|
Sign up to set email alerts
|

The competitive release kinetics and synergistic antibacterial characteristics of tea polyphenols/ε‐poly‐l‐lysine hydrochloride core–shell microcapsules against Shewanella putrefaciens

Abstract: To obtain the antibacterial agents with long-acting and slow-release properties, the microcapsules were prepared with tea polyphenols (TP), ϵ-poly-L-lysine hydrochloride (ϵ-PL) and TP/ϵ-PL as core materials. Meanwhile, the microcapsules were characterised, their release properties were measured, and their antimicrobial mechanisms against Shewanella putrefaciens were studied. At the initial release phase, TP and ϵ-PL are competitively released from the composite microcapsules. The release of TP and ϵ-PL is both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…They may also function indirectly as antioxidants through their effects on transcription factors and enzyme activities (Yan, Zhong, Duan, Chen, & Li, 2020). These compounds in green tea protect against a large amount of diseases, such as reduction the risk of cardiovascular disease (Fang et al, 2019; Pang et al, 2016), cancers (Bae, Kumazoe, Yamashita, & Tachibana, 2017; Wang, Cui, et al, 2020), anti‐inflammatory (Musial, Kuban‐Jankowska, & Gorska‐Ponikowska, 2020; Rha et al, 2019), high blood pressure (Li et al, 2019), antibacterial properties (Pang et al, 2016; Yang et al, 2020), and immune function (Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They may also function indirectly as antioxidants through their effects on transcription factors and enzyme activities (Yan, Zhong, Duan, Chen, & Li, 2020). These compounds in green tea protect against a large amount of diseases, such as reduction the risk of cardiovascular disease (Fang et al, 2019; Pang et al, 2016), cancers (Bae, Kumazoe, Yamashita, & Tachibana, 2017; Wang, Cui, et al, 2020), anti‐inflammatory (Musial, Kuban‐Jankowska, & Gorska‐Ponikowska, 2020; Rha et al, 2019), high blood pressure (Li et al, 2019), antibacterial properties (Pang et al, 2016; Yang et al, 2020), and immune function (Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the PUL-CMC composite coatings could effectively reduce the accumulation of volatile bases and delay the spoilage of sea bass, and this may be due to the barrier property of the PUL-CMC coating, the antioxidant activity of GA and the antibacterial activity of PL. 16,23,25 In addition, it should be noted that the pH values in PUL-CMC-GA-PL exhibited a lower pH value than other groups during storage. This may be due to the addition of GA and PL enhancing the antioxidant or antibacterial activities of the PUL-CMC coating, and a synergistic effect on the delay of sh spoilage might exist between GA and PL.…”
Section: Ph Valuesmentioning
confidence: 96%
“…24 The PL exhibits a broad spectrum of antibacterial activity against Gram-negative and Gram-positive bacteria, yeasts and molds. 24,25 However, PL possesses a poor antioxidant property, which limits its applications in food manufacturing and preservation processes. Therefore, if PL is combined with a good antioxidant such as GA, good antioxidant and antibacterial activity will be obtained, which increases its applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more and more chemical preservatives were used to inhibit the growth of bacteria and prolong the fish shelf life because of its low cost, simple process and wide application (Tang et al ., 2018). However, in recent years, with the emergence of potential food safe problems of chemical preservatives, biological preservatives have drawn increasing attention (Pateiro et al ., 2018; Yang et al ., 2020a). The biological preservatives can be divided by source into plant source preservatives (e.g.…”
Section: Introductionmentioning
confidence: 99%